2005
DOI: 10.1007/s11273-004-7525-6
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate community structure across a wetland hydroperiod gradient in southern New Hampshire, USA

Abstract: We conducted a field study to examine the influence of hydroperiod and concomitant changes in abiotic (wetland size, pH, conductivity, dissolved oxygen and water temperature) and biotic (predatory fish presence) characteristics on macroinvertebrate communities in isolated wetlands in southern New Hampshire. Invertebrates were sampled using dipnet sweeps in 42 wetlands with short (<4 months), intermediate (4-11 months) or long (permanent) hydroperiods in 1998 and 1999. We found that invertebrate genera richness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2
17

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 43 publications
1
37
2
17
Order By: Relevance
“…Studies on reservoirs conducted in different parts of the world have shown that environmental features of both large and small reservoirs, such as age, area, vegetation structure (e.g., density and the proportion of the surface area covered) and water permanence (Tarr et al 2005, for larvae; Kadoya et al 2004Kadoya et al , 2008, for adults) commonly influence the richness of odonate larvae (Oertli et al 2002, Carchini et al 2007, Maltchik et al 2010). These features are also remarkably influenced Neotrop.,vol.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on reservoirs conducted in different parts of the world have shown that environmental features of both large and small reservoirs, such as age, area, vegetation structure (e.g., density and the proportion of the surface area covered) and water permanence (Tarr et al 2005, for larvae; Kadoya et al 2004Kadoya et al , 2008, for adults) commonly influence the richness of odonate larvae (Oertli et al 2002, Carchini et al 2007, Maltchik et al 2010). These features are also remarkably influenced Neotrop.,vol.…”
Section: Discussionmentioning
confidence: 99%
“…We sampled water-column macroinvertebrates using a D-shaped sweep net with a 30 cm opening and 1 mm mesh size. Many previous studies (Bolduc & Afton 2003, Batzer et al 2004, Nicolet et al 2004, Tarr et al 2005, Hornung & Foote 2006, Kratzer & Batzer 2007 have found a D-shaped sweep net is an effective sampling method for macroinvertebrate sampling in ponds. We conducted a total of 10 continuous sweeps, each of 2 m long (surface covered 6 m 2 ; Bolduc & Afton 2003) at a randomly selected point near the edge of each pond.…”
Section: Aquatic Macroinvertebrate Sampling and Identificationmentioning
confidence: 95%
“…Protracted water permanence may provide nutrients (Lawler & Dritz, 2005) and extended habitat availabilities for aquatic invertebrates, thereby promoting biodiversity and species richness (Collinson et al, 1995;Tarr et al, 2005;Boulton, 2003). However, our two study areas differed not only in terms of water management practices but also in (i) land use in the tracts surrounding the fields, (ii) the extent of agrochemical usage, and (iii) water irrigation systems, which we did not evaluate in this study.…”
Section: Discussionmentioning
confidence: 91%